The Politics of Islamic Criminal Law in Indonesia(A Critical Analysis) - Mohamad Rapik (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Indonesia is well known as the country where Muslims are the majority. However, never has Islamic lawbecome the priority especially after the Indonesian independence. Therefore, the uproar calls for theapplication of Islamic are law still echoing until today. Though the state has answered those calls andsuccessfully applied Islamic law as part of the national legislation as seen, for example, in marriage law,Islamic banking law, law on hajj etc, it still fails to acknowledge the Islamic penal law to some extent.The paper would elaborate the problem of the politics of Islamic penal law in Indonesia. By analyzing thepolitics of Islamic penal law critically, this paper hopes to expose the problem behind the phenomenon.For this purpose, Islamic methodology through “maqashid syari’ah” (purposes of Islamic syariah) isneeded in order to see how Islamic law should work in the modern era and contextually stand side-by-sidewith the local need.